Analysis of Investment Risk and Share Return in Coal Mining Companies Listed on IDX for The Period 2019-2021 - Andi Dwi Wulandari; Muh. Ichwan Musa; Nurman; Anwar Ramli; Hety Budiyanti (PT. Maju Malaqbi Makkarana, 2023)
This research is to determine the level of investment risk and stock returns as well as grouping efficient shares and inefficient shares of coal mining companies through the Capital Asset Pricing Model (CAPM) method for the 2019-2021 period. The research method used is descriptive method with a quantitative approach, while the data analysis method uses the Capital Asset Pricing Model (CAPM) method. The results showed that there were 8 shares of coal mining companies with a beta (systematic risk) value of greater than 1 (β > 1), and 16 shares of companies with a beta of less than 1 (β < 1. The highest RI was found in HRUM shares with a rate of return of 0.07650 or 7.65%, while the lowest Ri is found in BOSS shares with an average rate of return of -0.06000 or - 6%. The highest E(Ri) value is found in DOID shares with a value of 0.00177 or 0.18%, while the lowest E(Ri) is found in GEMS companies with a value of 0.00126 or 0.13%. There are 16 shares of coal mining companies which are classified as efficient shares consisting of shares of ADRO, BSSR, BYAN, DOID, DSSA, FIRE, GEMS, iHRUM, INDY, iITMG, MBAP, MYOH, iPTRO, SMMT, iTOBA, and BRMS, as well as 8 inefficient stocks namely ARII, BOSS, BUMI, DEWA, ​​GTBO, KKGI, PTBA, and SMRU.